Resilient Consensus of Multiagent Systems Against Denial-of-Service Attacks - Zuo, Zhiqiang; Cao, Xiong; Wang, Yijing; Zhang, Wentao (IEEE transactions on systems, man, and cybernetics. Systems, 2022)
This article studies the consensus problem of multiagent systems (MASs) subject to Denial-of-Service (DoS) attacks from the perspective of control. The considered DoS attacks blocking the information exchange in the group of agents pose limitations on the frequency and the duration of them. A distributed observer-based controller is proposed to reconstruct the states of the agents. We prove that MASs under DoS attacks can still achieve consensus by the proposed controller. The scenario where DoS attacks simultaneously jam both the communication networks associated with the controller and the observer is also addressed, and a sufficient condition is obtained to maintain the consensus performance of MASs. Finally, numerical simulations are provided to illustrate the theoretical results.